Penyitaan Aset Tindak Pidana Korupsi Pada Tahap Penyidikan Sebagai Upaya Pertama Dalam Pengembalian Kerugian Negara - Novalin Noya; Elsa Rina Maya Toule; Deassy Jacomina Anthoneta Hehanussa (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: Confiscation of assets of criminal acts of corruption at the investigation stage as the first effort in recovering state losses within the Prosecutor's Office, especially at the Maluku.Purposes of the Research:  This study aims to analyze and explain what are the legal considerations and explain what factors are the obstacles faced by prosecutors in confiscating assets in corruption cases.Methods of the Research: The type of research used is normative legal research, meaning research that has an object of study on rules or regulations. The problem approach is in the form of a Legislative Approach (Statute Approach), a conceptual approach (Conceptual Approach), and a case approach (Case Approach). The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The collection technique is done through literature study and qualitative analysis of legal materials.Results of the Research: The results of the study indicate that the return of state assets has not been optimal because there are still many state losses that have not been returned because there are several weaknesses so that improvements need to be made to realize good governance. In addition, there are still inhibiting factors or obstacles in returning the assets of the criminal act of corruption which is marked by the lack of good coordination in the legal structure, the lack of human resources in the internal prosecutor's office, facilities and infrastructure, and the lack of participation from the public who tend to be apathetic. To overcome the obstacles and obstacles in the settlement of cases of criminal acts of corruption closely related to the confiscation of assets carried out by the Prosecutor's Office, cooperation and coordination with related technical fields are needed both in the internal and external environment.